Use of animal fiber-reinforcement in construction materials: a review (2024)
Although natural fibers (NFs), among which animal fibers (AFs) are found, have been used for millennia as reinforcement scheme of some construction materials (CMs), it is not until recent decades when scientific studies have been carried out to quantitively evaluate the impact of adding NFs into CMs, but with a special focus on vegetal fibers (VFs) over AFs. Nevertheless, there have been several studies addressing the use of AFs in different CMs and, therefore, the need of a systematic review study is evident. To contribute to this research gap, this paper presents a comprehensive review study addressing available scientific information of different types of AFs (e.g., sheep wool fibers (SWFs), chicken feathers fibers (CFFs), human hair fibers (HHFs), pig hair fibers (PHFs), silk fibers (SFs), and dog hair fibers (DHFs)) and also their use in four specific different CMs matrices (i.e., cementitious, gypsum, soil and polymer matrices). This comprehensive search was conducted in Web of Science and Science Direct, two of the largest and more prestigious scientific databases, using specific keywords and Boolean operators and the selection of the papers was based on the provision of enough quantitative information of the mixtures (e.g., specific characteristic and dosages of AFs and matrix used) as well as experimental findings. As a result of this study, organized, summarized and sufficient information is provided to support the positive use of AF as reinforcement scheme to improve some physical/thermal/mechanical/damage/durability properties of CMs by taking advantage of the abundance of these resources worldwide. Moreover, the use of AFs might also provide environmental benefits and cost reductions, which are global objectives within the construction sector. Finally, this review study found that there are still several research gaps in the use of particular AFs (e.g., DHFs) as well as combinations between the AFs and the CMs addressed in this study (e.g., effects of PHFs in polymer matrices) and these gaps are recommended as future studies.